ANALISIS PENGARUH PENGGUNAAN SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Kasus Dinas Pekerjaan Umum dan Penataan Ruang Provinsi Bengkulu) - Yesi Indian Ariska; Nia Indriasari (Management Insight: Jurnal Ilmiah Manajemen, 2017)
The purpose of this research aimed to test the influence of the implementation of region management information system on the quality of financial statement of regional government at Department of pekerjaan umum and penata an ruang province Bengkulu. The research population was 25 people who are the employees at this department. Research data were questionnaire as the primary data. The simple linear regression analysis was the technique of analysis of this research.Research result showed that the implementation of region management information system influenced significantly to the quality of financial statement of regional government at Department of of pekerjaan umum and penataan ruang province Bengkulu.. It was approved by the value of determinant coefficient which was 75.3%. It meant that the quality of financial statement was influenced 75.3% by the spatial planning region management information system.Keywords: regional government, management information system, quality, financial.